Factors affecting customers’ purchasing decision on Johnson’s Baby Products in Vietnam - Pham , Van Tai; Nhi, Pham Ngoc Yen (International Journal of Psychosocial Rehabilitation, 2020)
The turnover of the market of products and services for children in Vietnam has been predicted to reach a scale of 7 billion USD, with a growth rate of 30-40%. Detailed, according to Nielsen, with the middle class growing strong in Vietnam, the needs of parents for children's products will be increasingly higher in both quantity and quality. In the developed markets, where the fertility rate is low and the types of baby care products are saturated, growth will be motivated by innovation and high levels of product chemistry, while in the growing markets, the rising demand will be the biggest growth motivation. Today, Johnson & Johnson is one of the largest health care companies in the world. In 2018, the company reported more than $81,6 billion in sales. However, in 2017, J&J began to face lawsuits over asbestos exposure from contaminated talcum powder products. This event greatly affects the reputation of the brand in the Vietnam market and of course the revenue of the baby sector. The more challenging and difficult it is for Johnson's Baby in retaking the trust and the customer's favor. In order to write the article, consulting several sources such as books, newspapers, magazines, reports as well as other articles was necessary. Analysis, statistic, prediction, the application is the essential methods which were used to express the topic. The authors used the SWOT analysis method to assess the factors affecting customers’ purchasing decision on Johnson’s Baby Products in Vietnam. Some recommendations for developing strategies of Johnson Baby Vietnam have been proposed from the above analysis. The article consists of four root factors which are: firstly, the Vietnamese social; secondly, the psychologic of Vietnamese customers; thirdly, the factors belongs to customers’ personal; eventually, the Johnson Baby marketing actions. Relating to the factors affecting customers’ purchasing decision, the article will reflect the considerable factors of the Vietnamese customers or market on Johnson baby products surveying during the period from 20th September 2019 to 21st October,2019.